Multiple Paths of Rural Transformation and Its Driving Mechanisms Under the Perspective of Rural–Urban Continuum: Taking Suzhou, China as an Example - Ping Xu; Han Mu; Jingwei Shao; Yuan Yuan (Land, 2025)
Under the context of urban–rural integration, exploring the complex process and general patterns of rural transformation is a critical issue for advancing sustainable rural development. This study develops a theoretical framework for rural transformation from the perspective of the rural–urban continuum. By analyzing the shifting urban–rural dominance relationships across different periods in township units, we extracted the main paths of rural transformation. Empirical analysis of 46 townships in Suzhou, China from 1990 to 2020 reveals the following key findings: (1) The urban–rural dominance relationships in township units have undergone an evolution from “differentiation to intensification to stabilization” over the past three decades, shaped by two pivotal moments—the Sunan Model and the New Sunan Model. (2) By combining four modes (enhancement, weakening, stabilization, and exchange) across different time periods, three primary paths of rural transformation in Suzhou emerge: a continuous stabilization type, a mid-late enhancement type, and a mid-term weakening type. (3) The spatial heterogeneity of the driving mechanisms is particularly evident in the northern region’s modernization of agriculture, the southern region’s characteristic fisheries, the western region’s localized urbanization, and the eastern region’s integration of industry, city, and population (I-C-P). The diverse paths identified in this study offer a deeper understanding of the simplified macro trend in which rurality weakens and urbanity strengthens, providing valuable insights for the tailored promotion of rural revitalization.